2018
DOI: 10.1590/s1980-6574201800010013
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of low or vigorous levels of physical activity on body composition, hemodynamics and autonomic modulation in Down syndrome subjects

Abstract: Aim: We aimed to evaluate the effect of low and vigorous levels of physical activity in body composition, hemodynamics and autonomic modulation in subjects with Down syndrome (DS). Methods: We evaluated 13 healthy subjects without DS (control group), 15 sedentary subjects with DS, (SED DS group), nine with DS with low intensity levels of physical activity (LIDS) and 12 with DS with vigorous levels of physical activity (VIDS). The physical activity level was measured using the IPAQ questionnaire. Body compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…Heart rate variability (HRV) consists of the fluctuations in R-R interval (iRR) between successive heartbeats defined by the distance between two R-waves on the electrocardiogram 1,2 . HRV has been used either in sports or in clinical settings as a proxy of the cardiac autonomic function 3,4 . In this sense, different HRV methods and indices have been proposed to evaluate the parasympathetic activation or its withdraw associated with various physiological conditions such as exercise 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability (HRV) consists of the fluctuations in R-R interval (iRR) between successive heartbeats defined by the distance between two R-waves on the electrocardiogram 1,2 . HRV has been used either in sports or in clinical settings as a proxy of the cardiac autonomic function 3,4 . In this sense, different HRV methods and indices have been proposed to evaluate the parasympathetic activation or its withdraw associated with various physiological conditions such as exercise 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cunha et al (19) No estudo de Seron et al (18) , os treinos aeróbios e resistido não foram capazes de aumentar o consumo máximo de oxigênio.…”
Section: Discussionunclassified
“…Of the remaining 53 articles, 33 did not meet the inclusion criteria, leaving 20 to undergo a full-text analysis. Finally, 5 more articles were discarded for specified reasons (see Figure 1), leaving a total of 15 studies to be included in the systemic review [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. One additional study was identified by checking the references within these 15 studies.…”
Section: Selection Of the Studiesmentioning
confidence: 99%